Forcing Subsets for Î³c-sets and Î³t-sets in the Lexicographic Product of Graphs (European Journal of Pure and Applied Mathematics, 2019)
In this paper, the connected dominating sets and total dominating sets in the lexicographic product of two graphs are characterized. Further, the connected domination, total domination, forcing connected domination and forcing total domination numbers of these graphs are determined.